2011
DOI: 10.1017/s0022029911000069
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of enterotoxigenicEscherichia colivaccine for bovine clinical mastitis

Abstract: An enterotoxigenic Escherichia coli (ETEC) vaccine designed to prevent diarrhoea was inoculated into dairy cows, and the occurrence of clinical mastitis was investigated for 2 years. Half of 480 cows in five farms were subcutaneously inoculated with ETEC vaccine (Imocolibov) twice with a 1-month interval in 2007 and 2008. Fisher's exact test and survival (time to event) analysis with the log-rank test were used to compare vaccinates and controls. In 2007, there was no significant difference in the incidence ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Additionally, the immune protection efficacy of the E. coli J5 vaccine tends to decrease during peak lactation in dairy cattle ( 97 ). Another study revealed that vaccination against enterotoxigenic Escherichia coli (ETEC) reduced death or culling due to mastitis, but did not have a preventive effect on the development of mastitis ( 98 ).…”
Section: The Current Status Of Research On Major Bovine Vaccinesmentioning
confidence: 99%
“…Additionally, the immune protection efficacy of the E. coli J5 vaccine tends to decrease during peak lactation in dairy cattle ( 97 ). Another study revealed that vaccination against enterotoxigenic Escherichia coli (ETEC) reduced death or culling due to mastitis, but did not have a preventive effect on the development of mastitis ( 98 ).…”
Section: The Current Status Of Research On Major Bovine Vaccinesmentioning
confidence: 99%
“…These cows were fed a TMR and milked at 0900 and 1600 h. Seven cows were subcutaneously inoculated with 5 mL of ETEC vaccine (Imocolibov, Merial; Scientific Feed Laboratory Co. Ltd., Tokyo, Japan) 3 wk before LPS challenge, and the remaining 7 did not receive treatment. The ETEC vaccine used in this study was an inactivated aluminum hydroxide and saponin-added vaccine against neonatal colibacillosis of calves and lambs, supplied as a suspension for injection (Morimoto et al 2011). The daily milk yield just before LPS challenge was 40.2 ± 2.7 kg (mean ± SE) in vaccinated cows and 33.6 ± 5.2 kg in control cows.…”
Section: Animals and Lps Challengementioning
confidence: 99%
“…In Europe and North America, mastitis vaccines developed from Escherichia coli O111:B4 strain J5 (Overbeek et al, 1987) or Salmonella typhimurium Re-17 mutant (McClure et al, 1994) have been investigated for their efficacy (Hogan and Smith, 2003;Wilson et al, 2007). A previous study reported the use of an inactivated enterotoxigenic Escherichia coli (ETEC) vaccine, designed to prevent diarrhea, and to reduce death and culling due to mastitis (Morimoto, et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of the current advocacy of resistance reduction initiatives, methods using biological agents against mastitis are being developed, including phage therapy, antimicrobial therapy, antibody therapy, nonspecific immune boosting prophylaxis and vaccine prophylaxis. In particular, to effectively prevent and control the occurrence of bovine mastitis and to prevent the further effects of antibiotics on the ecosystem, the development of new vaccines has become a critical research direction [19][20][21][22][23]. At present, bovine mastitis E. coli vaccine is available from the U.S. company Schotten and from the Spanish company Ophthalmology.…”
Section: Introductionmentioning
confidence: 99%